Composition considerations for fluid teams: a review - Driskell, Tripp; Funke, Gregory; Tolston, Michael; Capiola, August; Driskell, James (Frontiers in Psychology, 2024)
The need exists to better understand how to comprise fluid teams—teams that are assembled on short notice, from members with little to no familiarity, who come together to carry out a time-limited task, and then disband. Due to the ever-increasing complexity of the modern workplace, the demand for these types of fluid teams is growing in task domains such as the military, aviation, healthcare, and industry. The aim of this paper is to review the team composition literature to shed light on composition considerations for forming fluid teams.